PULMONARY ARTERY THROMBOEMBOLISM. (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
Pulmonary artery thromboembolism (PATE) is a life-threatening condition resulting from the obstruction of the pulmonary artery or its branches by a blood clot. It is considered one of the most serious cardiovascular emergencies due to its sudden onset and high mortality rate. This article discusses the etiology, pathogenesis, clinical presentation, diagnostic approaches, and treatment methods of pulmonary embolism. Special attention is paid to risk factors such as immobility, surgical interventions, cancer, and thrombophilia. The importance of early diagnosis and prompt anticoagulant therapy in reducing complications and improving patient outcomes is emphasized. The article also reviews modern imaging techniques and prevention strategies to reduce the incidence of PATE in at-risk populations.